Interactive PowerPoint Based on Discovery Learning for Teaching the Area of Plane Figures in Grade V Elementary School Mathematics - I Kadek Dwi Arta; I Wayan Wiarta; Dewi Anzelina (Universitas Pendidikan Ganesha, 2025)
Mathematics learning in elementary school still faces challenges due to the abstract nature of its concepts, particularly in the topic of plane figures area, which leads to low students’ conceptual understanding. This study aims to examine the feasibility and effectiveness of an interactive PowerPoint media based on Discovery Learning to improve students’ mathematics learning outcomes. The study employed a Research and Development approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects involved elementary school students as media users, as well as experts in instructional design, instructional planning, media, and subject matter as validators. Data were collected through expert validation sheets, individual and small-group trial questionnaires, and learning achievement tests. The research instruments consisted of questionnaires, assessment rubrics, and posttest items. Data analysis was conducted using descriptive quantitative methods to assess media feasibility and a t-test to examine its effectiveness. The results showed that the developed media was considered feasible, with validation scores of 95% from instructional design experts, 80% from instructional planning experts, 91.67% from media experts, and 91.67% from subject matter experts. Individual trials obtained a score of 89%, while small-group trials reached 84%, both categorized as good. The effectiveness test indicated an average posttest score of 93, exceeding the minimum mastery criterion of 75, with a t-value of 12.449 > 2.10. The conclusion confirms that the interactive PowerPoint media based on Discovery Learning is valid, practical, and effective. These findings imply that the media can be utilized by teachers as an alternative approach to create active, engaging, and learning experiences aligned with 21st-century competency demands.